Enhancing Financial Management Competence Through Human Resource Management Practices: Insights From Micro, Small, And Medium Enterprises - Taufan Herjanto (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This qualitative study aims to explore the relationship between Human Resource Management (HRM) practices and the enhancement of financial management competence within Micro, Small, and Medium Enterprises (MSMEs). The research model is grounded in HRM theories and financial management frameworks. A purposive sampling technique is employed to select participants from diverse MSMEs. Data analysis involves thematic analysis, focusing on identifying patterns and themes within the collected qualitative data. The findings reveal that strategic HRM practices such as recruitment, training, and performance appraisal significantly contribute to improving financial management competence in MSMEs. Additionally, fostering a culture of continuous learning and skill development emerges as a crucial factor. This study provides valuable insights for MSMEs aiming to strengthen their financial management capabilities through effective HRM strategies.